The Bon sman sgrub ritual - Sehnalova, A (2013)
The thesis deals with the Tibetan healing mendrub (sman sgrub) ritual as performed by the contemporary exile Bonpo community at the Triten Norbutse Monastery, Kathmandu, Nepal in December 2012. The ritual is described and analysed, particular attention is given to its medical component. The research is based on fieldwork, textual analysis and close work with Tibetan traditional scholars, including a doctor of Tibetan medicine. The axis of the thesis is the specific "material core of the ritual", the so called medicine (sman) or mendrub medicine (sman sgrub kyi sman), its preparation, the processes it undergoes in the course of the ritual as well as approaches to understanding it and the ritual as a whole: The generated empowered medicine as a miraculous substance represents a universal remedy and the ritual performance pacifies the universe. On the highest spiritual level, both work solely as a symbolic support on one’s path towards enlightenment. The Tibetan medical system derives from different spheres of knowledge and is tightly tied to religion, philosophy, cosmology and tantric practices. As such it forms a very complex unit all parts of which become materially expressed and "replayed" by the ritual. Within the cosmological framework the medicine, both medical concepts and medicinal substances, as well as the act of healing become 'mandalised'. Similarly, human body and Buddhist philosophical concepts are fitted into the mandalic organizational scheme. Its purpose is to embrace and position every entity in order to make the whole unit, i.e. body, universe etc., balanced.